Методы и направления программной реализации расчетных методик оценки ЭМС РЭС - Николаев, И. М.; Закора, А. В.; Зверев, В. П. (ХНУРЭ, 2008)
Basic results of creation of a softwire for estimation of the electromagnetic compatibility (EMC) in the groups of .radio-electronic vehicles (REV) operating in various frequency range are reduced. Created softwire provides the EMC estimation for different conditions of REV receiver and transmitter functioning and for different parameters of antenna-feeder pathes.